INCREASING STUDENTS' DISCUSSION CREATIVITY IN LEARNING ISLAMIC EDUCATION THROUGH A COOPERATIVE APPROACH MODEL - Indah Setiorini; Rahmad Risan (Media Inovasi Pendidikan dan Publikasi, 2023)
A learning method that has the potential to develop social aspects is discussion. The purpose of this classroom action research is to find out whether the cooperative discussion method can improve students' creativity. This type of research is Classroom Action Research which consists of planning, implementation, observation, and reflection. The research subjects were fourth grade students of SDN Puhrubuh 1 Kec. Semen Kab. Kediri. as many as 15 students. This research was conducted in two cycles. The action in this study is the use of cooperative models in improving the creativity of group discussions. The research data was taken based on observation during PAI learning. Furthermore, the collected data were analyzed descriptively quantitatively. From the results of the study, it can be concluded that the use of cooperative models in group discussions can increase students' creativity in learning PAI class IV SDN Puhrubuh 1 Kec. Semen Kab. Kediri. This can be seen from the average value of observations based on observation indicators from cycle I to cycle II increased by 35% for each observation indicator.